IMPLEMENTASI AJARAN KASIH KRISTUS: PELATIHAN ALTRUISME UNTUK MEMBANGUN CARING BEHAVIOR REMAJA DI SMA SWASTA X JAKARTA - Dariyo, Agoes; Andrianputra, Ezra (Jurnal PKM Setiadharma, 2024)
The main problem of Generation Z is their indifference to the social environment, because they have been spoiled by advances in information and communication technology, so they have no concern for the interests of other people. This community service activity takes the form of altruism training which aims to develop caring behavior in generation z teenagers at X Private High School in Jakarta. The number of participants was 95 students (56 women and 49 men). The implementation method is carried out in pre-activity, activity and post-activity stages. Pre-activity issues were deepened through interviews with school principals, guidance and counseling teachers and lesson teachers. The activity period is providing altruism training. After the activity, namely interviewing the school principal, guidance and counseling teachers, lesson teachers and training participants. Data collection techniques through interviews, observation and documentation studies. Analysis technique with a qualitative approach. The results of the activity concluded that cognitively, altruism training can provide knowledge of helping behavior based on empathy for other people's conditions, so that they can develop caring behavior to show helping (prosocial) behavior towards other people.